2017
DOI: 10.1017/s0033291716003299
|View full text |Cite
|
Sign up to set email alerts
|

Structural correlates of trait impulsivity in patients with bipolar disorder and healthy controls: a surface-based morphometry study

Abstract: The findings indicate that the left prefrontal cortex plays a cardinal role in trait impulsivity of healthy individuals. Patients with BD have a different structural correlate of trait impulsivity in the right insula. However, the use of various psychotropics in patients with BD may limit our interpretation of BD findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
3
16
2
Order By: Relevance
“…In addition, findings from recent structural neuroimaging studies (e.g., Cho et al, 2013;Tu, Kuan, Li, & Su, 2017) suggest that only the grey matter volume in LDLPFC but not RDLPFC correlates with self-report measures of impulsivity. The third possible explanation is that the rTMS modulation effect on DLPFC may be only reflected by the tasks measuring proactive rather than reactive motor inhibition (Brevet-Aeby et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, findings from recent structural neuroimaging studies (e.g., Cho et al, 2013;Tu, Kuan, Li, & Su, 2017) suggest that only the grey matter volume in LDLPFC but not RDLPFC correlates with self-report measures of impulsivity. The third possible explanation is that the rTMS modulation effect on DLPFC may be only reflected by the tasks measuring proactive rather than reactive motor inhibition (Brevet-Aeby et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Studies on the neurobiological correlates of impulsive traits have the potential to uncover other underlying processes that may contribute to impulsive and risky phenotypes. Extant neuroimaging research has demonstrated associations between brain structure and impulsivity in adults [16][17][18]. For example, studies have shown positive correlations between self-reported impulsivity and volume of the anterior cingulate gyrus and dorsolateral prefrontal cortex [19].…”
Section: Neuroanatomical Correlates Of Impulsivitymentioning
confidence: 99%
“…Dalley and Robbins 2017), attention-deficit hyperactivity disorder (Ahmad andHinshaw 2017, Martel et al 2017), antisocial personality disorder (González et al 2016, Martel et al 2017, and bipolar disorder (Tu et al 2017), this finding supports the notion that the beneficial effects of nature may be especially evident in those individuals who possess greater vulnerability to mental-health issues. The implications of these results are twofold.…”
Section: Associations Between Momentary Mental Well-being Score In mentioning
confidence: 75%
“…One of the aims of our project was to explore how the impact of the surrounding built environment on the mental well-being of an individual might depend on their vulnerability to developing mental-health issues. For this reason, we included an assessment of trait impulsivity, a well-established psychological measure of one's tendency to behave with little forethought, reflection, or consideration of the consequences (Mayhew and Powell 2014 (Ahmad andHinshaw 2017, Martel et al 2017), antisocial personality disorder (González et al 2016, Martel et al 2017, and bipolar disorder (Tu et al 2017). We used the data to test three related hypotheses: (1) exposure to natural features, including trees, the sky, birdsong, and water, would be associated with higher levels of momentary mental wellbeing; (2) these effects would still be evident in subsequent assessments, in which people are no longer exposed to trees, the sky, birdsong, and water, indicating time-lasting benefits;…”
Section: The Urban Mind Toolmentioning
confidence: 99%